Protein-protein interactions during Japanese encephalitis infection - Magdline Sia, Henry Sum. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Japanese encephalitis virus is an important etiological for encephalitis in most parts of Asia. The events that leads to a productive infection of JEV are however not thoroughly understood. Here in this study we investigated the interaction between JE viral proteins and cellular host proteins when infection takes place.